IMPLEMENTASI TEAM-TEACHING DALAM PEMBELAJARAN PENDIDIKAN KEPENDUDUKAN DAN LINGKUNGAN HIDUP YANG TERINTEGRASI - Masruri, Muhsinatun Siasah; SURYO, DYAH RESPATI (Universitas Negeri Yogyakarta, 2002)
Abstract So far, the teaching of environment and Population Education at high school has not been effective yet. The purpose of this study was to find out the effectiveness of team teaching that wasintegrated in all relevant subject matters of Environment and Population Education. This study was conducted within a pretest-posttest with nonrandom control group and experimental design. The subject consisted of 77 students as the experimental group and 64 students as the control group. The analysis on the gain scores reveal hat the team teaching is significantly more effective than the traditional teaching(p0.05). Keywords: team teaching, integrated approach, environment and population education